Drying of Red Chili Pepper (Capsicum annuum L.): Process Kinetics, Color Changes, Carotenoid Content and Phenolic Profile - Andrzej Krzykowski; Stanisław Rudy; Renata Polak; Beata Biernacka; Anna Krajewska; Emilia Janiszewska-Turak; Iwona Kowalska; Jerzy Żuchowski; Bartosz Skalski; Dariusz Dziki (Molecules)
Studies were conducted focusing on the drying of chili pepper fruits (Capsicum annuum L.), cultivar Cyklon, using convective (AD), convective-microwave (AMD), vacuum (VD), and freeze-drying (FD) methods. The influence of the drying method and temperature on the kinetics of the process and selected quality attributes of the dried product were evaluated. It was demonstrated that the Midilli model best described the drying kinetics for all methods across the entire measurement range. FD and VD produced dried products with the highest brightness and the greatest value of the a* color parameter. The lowest b* color parameter was observed for the product dried using FD at 40 °C, while the highest b* value was noted for samples dried using AMD (100 W) at 60 °C. The highest carotenoid retention was achieved with the FD method at 40 °C, while the lowest carotenoid content was found in the product obtained using the AMD method (100 W) at 60 °C. The smallest losses of capsaicinoids were observed after FD drying at 40 °C, while the largest were found for AMD (100 W) at 60 °C. The analysis of chili pepper fruit extracts revealed the quantitative composition of 12 main phenolic compounds using the UHPLC-UV method. The highest polyphenol content was obtained with FD, while the lowest total polyphenol content was recorded after AD. Regardless of temperature, the total flavonoid content was highest in extracts from FD products, and the lowest flavonoid content was found after AMD at 100 W. For all drying methods analyzed, the total flavonoid content in the pepper extracts decreased with increasing temperature.